Lived Experiences of Cancer Patients Who Chose to Stop Receiving Treatment - Amreen Ali; Neena Kohli; Shreshtha Yadav (The Beryl Institute, 2024)
The study aimed to understand the lived experience of cancer patients who abandon treatment. Four semi-structured interviews were conducted, and the data was examined using interpretative phenomenological analysis. It resulted in four superordinate themes: (i) 'Lack of knowledge about cancer' dealt with patients' knowledge and perceptions about their cancer. (ii) 'Hopelessness with oneself and God.' (iii) 'Distress caused by numerous cancer-related issues' captured the challenges faced by cancer patients. The last superordinate theme, (iv) Patient dissatisfaction with physicians and treatment' dealt with cancer patients' interaction with and expectations from their oncologists and the medical staff. It was found that these factors played a crucial role in treatment abandonment. The decision to discontinue treatment can be attributed to patient dissatisfaction with the physician and treatment. This dissatisfaction was caused by misinformation about the disease, treatment, and distress. Since the patients were familiar with each other as they went for chemotherapy in the same hospital, the decision to abandon the treatment of one participant may have influenced the other participant. For policymakers, it is critical to understand that a 'dissatisfied patient' may abandon treatment at any time during their cancer trajectory, consequently affecting the mortality, morbidity, and economic burden of the country.